MtnBD Is a Multifunctional Fusion Enzyme in the Methionine Salvage Pathway of Tetrahymena thermophila - Nakano, Toshihiro; Ohki, Izuru; Yokota, Akiho; Ashida, Hiroki (PLOS ONE, 2013)
To recycle reduced sulfur to methionine in the methionine salvage pathway (MSP), 5-methylthioribulose-1-phosphate is converted to 2-keto-4-methylthiobutyrate, the methionine precursor, by four steps; dehydratase, enolase, phosphatase, and dioxygenase reactions (catalyzed by MtnB, MtnW, MtnX and MtnD, respectively, in Bacillus subtilis). It has been proposed that the MtnBD fusion enzyme in Tetrahymena thermophila catalyzes four sequential reactions from the dehydratase to dioxygenase steps, based on the results of molecular biological analyses of mutant yeast strains with knocked-out MSP genes, suggesting that new catalytic function can be acquired by fusion of enzymes. This result raises the question of how the MtnBD fusion enzyme can catalyze four very different reactions, especially since there are no homologous domains for enolase and phosphatase (MtnW and MtnX, respectively, in B. subtilis) in the peptide. Here, we tried to identify the domains responsible for catalyzing the four reactions using recombinant proteins of full-length MtnBD and each domain alone. UV-visible and 1H-NMR spectral analyses of reaction products revealed that the MtnB domain catalyzes dehydration and enolization and the MtnD domain catalyzes dioxygenation. Contrary to a previous report, conversion of 5-methylthioribulose-1-phosphate to 2-keto-4-methylthiobutyrate was dependent on addition of an exogenous phosphatase from B. subtilis. This was observed for both the MtnB domain and full-length MtnBD, suggesting that MtnBD does not catalyze the phosphatase reaction. Our results suggest that the MtnB domain of T. thermophila MtnBD acquired the new function to catalyze both the dehydratase and enolase reactions through evolutionary gene mutations, rather than fusion of MSP genes.